Empowerment of Psychotic Cases as an Effort to Restore Social Functioning for People with Social Welfare Problems (Case Study at the Sidoarjo Social Service and Rehabilitation Center) - Nur Khabibah; Mohtazul Farid (Polteknik Ilmu Pemasyarakatan, 2023)
Empowerment is a process to form empowered individuals over themselves. The empowerment model is one of the efforts to shape social functioning. The objectives of this study include two things. First, to find out the empowerment model applied by the Sidoarjo Social Service and Rehabilitation Center for people with psychotic type social welfare problems. Second, to determine the social functioning of people with psychotic type social problems after following the empowerment model. This research uses the ACTORS theory by Sarah Cook and Steve Macaulay supported the concept of social functioning. This research uses qualitative methods, case study approach. Data collection techniques through interviews, observation, and documentation. The technique of determining informants uses purposive sampling. Miles and Huberman model data analysis. Data validity techniques use source triangulation. The results of this study show that the empowerment model applied to psychotic type PMKS by the Sidoarjo Social Service and Rehabilitation Center consists of guidance, mental and spiritual, social, and skill training programs. Based on the research conducted, the program can form social functioning in psychotic type PMKS. This happens to psychotic PMKS who are still in the hall or return to the family. The first indicator in the concept of social functioning, evidenced by independence in getting a job. In the second indicator, the ability to perform tasks according to their status. The third indicator shows the initiative of action when experiencing problems.